Afterglow dynamics of plasma potential in bipolar HiPIMS discharges. (30th November 2021) - Avino, F; Manke, F; Richard, T; Sublet, A
Abstract: In bipolar magnetron sputtering, the plasma afterglow is initiated by switching the target bias from a negative to positive voltage. In the following, the plasma potential evolution in this configuration is characterized, being responsible for the ion acceleration at the substrate sheath potential fall, in particular in high power impulse magnetron sputtering (HiPIMS). A mass-energy analyzer and a Langmuir probe respectively measure the ion energies and the plasma/floating potential at different positions within HiPIMS discharges. A plasma potential drop and rise in the first 45  μ s of the afterglow is observed, settling in the plasma bulk towards values below the applied positive bias. The measured ion energies agree with the plasma potential values before and after the drop-rise. To gain more comprehensive insights into the mechanisms responsible for such a potential evolution, particle-in-cell Monte Carlo 3D simulations of bipolar direct current magnetron sputtering discharges are explored in equivalent geometries. Despite their average power being orders of magnitude lower compared to the HiPIMS configuration, a similar afterglow behavior is observed. This indicates that the measured dynamics are not specific to HiPIMS, but rather a feature of bipolar magnetron sputtering. The responsible mechanisms are studied further: the effects of various system parameters are decoupled, with the magnetic field configuration emerging as crucial for the plasma potential drop-rise dynamics and the associated re-ionization close to the target.